Batman character encyclopedia - Manning, Matthew K. (DK Publishing, 2016)
Presents images from the official DC "Batman" comic books showcasing a host of Batman's allies, neutral acquaintances, and foes in the DC universe, providing character information, statistics, history, equipment, skills, and abilities.